Clinico Hemato Biochemical Findings, Clinical Management, and Production Performance of Bovines with Late Pregnancy Indigestion (Type IV Vagal Indigestion). (13th April 2014) - Hussain, Syed Ashaq; Uppal, Sanjeev Kumar; Sood, Naresh Kumar; Mahajan, Shashi Kant
Abstract : This prospective study was conducted on 15 animals (eight buffaloes and seven cows), diagnosed with late pregnancy indigestion. Ten buffaloes and 10 cows served as the control group. The animals were in advanced pregnancy and had partial or complete anorexia, reduced water intake, loss of defecation or scanty faecal output, and mild to moderate dehydration. Heart and respiration rates were increased and rumen motility was reduced. Five animals had persistent tympany and moderate distension of left abdomen, and two animals each had bilateral abdominal distension and papple shaped abdomen. Neutrophil and lymphocyte counts were significantly higher and lower than the control values. Total bilirubin, AST, total protein, globulin, BUN, glucose, and lactate were significantly higher, and chloride and calcium were significantly lower than the control values. Levels of ALP, GGT, albumin, creatinine, cholesterol, triglyceride, fibrinogen, fibrinogen ratio, sodium, potassium, phosphorus, and magnesium did not differ significantly from the control values. Rumen chloride concentration was higher than the reference range. Majority of animals were managed symptomatically until parturition. There was no effect on fetal survival or milk yield in current and subsequent lactation. So, late pregnancy indigestion causes clinical and hemato biochemical alterations which require special consideration when treating diseased animals.